Investigating the transcriptional fingerprints of cocultured Saccharomyces cerevisiae and Lachancea thermotolerans in a model wine environment - Asmus, Justin Joseph; Naidoo-Blassoples, Rene Kathleen; Pérez-Torrado, Roberto; Bauer, Florian F. (Frontiers in Microbiology, 2026)
IntroductionWine fermentation is an evolutionarily relevant and relatively well described microbial ecosystem that was proposed as a model system to study mechanisms of interactions between wine yeast species. In this context, several studies have investigated phenotypic and molecular characteristics of yeast species when in two-species coculture, consisting of one strain of S. cerevisiae and a strain of another prevalent wine yeast species, including L. thermotolerans and T. delbrueckii.. Transcriptomic data generated in such studies have highlighted S. cerevisiae genes whose expression appeared to respond to the presence of other yeasts. However, these datasets diverge due to different growth conditions, differing inoculation strategies, the strains that were used and sampling time points.MethodsIn this work, a pooled analysis was conducted to combine and integrate datasets generated from previous studies involving interaction between S. cerevisiae and L. thermotolerans. Thirty-nine samples from three studies generated on Illumina or Ion Torrent sequencing platforms were individually re-assessed using iDEP for normalization and differential expression analysis (|log2FC| > 0, FDR ≤ 0.05). Recurring trends in the form of a core set of differentially expressed genes were identified. Deletion mutants of these genes were evaluated in a semi-high throughput assay to identify genes whose activity would specifically impact growth and fermentation performance in cocultures, and one S. cerevisiae gene, FIT2, whose deletion mutants consistently showed diverging phenotypes when in coculture, was further analyzed.Results and discussionThe results highlight pathways and genes consistently enriched in all studies, including copper ion import, transition metal and iron ion transport, cell wall mannoproteins and biogenesis as well as methionine and sulfur biosynthesis. Interestingly, FIT2 deletion in the original wine yeast wildtype strain (VIN13Δfit2) showed opposite, but still interaction specific, phenotypes when compared with the laboratory strains of the Euroscarf deletion library. Considering the evolutionary context of these strains and likely differences in cell wall mannoprotein composition, these data emphasize the challenges of gene annotation in an ecosystem relevant context. The findings reinforce observations from previous research, suggesting that FIT2 has a significant role in modulating interactions between species and highlighting specific DEGs from pathways that require further investigation in future coculture studies.